Histopathological Spectrum of Nephrectomies; a Single Centre Experience of over 14 Years (Journal of Renal and Hepatic Disorders, 2022)
Nephrectomy is conducted either as an open or a laparoscopic procedure for a variety of clinical indications. These include both neoplastic and non-neoplastic conditions, such as the non-functioning kidney. In many patients the final diagnosis is established on the histopathology of the retrieved kidney. In this study, retrospective analysis of data of last 14 years was studied pertaining to the number and indications of nephrectomy at the present study centre. Demographic and clinical details were assessed. Gross and microscopic histopathological details were recorded. Diagnosis was established on the basis of clinical features and histopathology. A total of 638 total nephrectomy specimens were received. Of these, 280 cases were of neoplastic and 358 of non-neoplastic lesions, with a male-to-female ratio of 1.21:1. The age range varied widely according to clinical manifestations. The age range in the present study was 5–84 years. Patients operated for non-neoplastic disorders were younger (mean age: 38.1 years) than those operated for neoplastic disorders (mean age: 54.4 years). Clear renal cell carcinoma (RCC) was the commonest RCC type (150 patients) followed by papillary RCC (51 cases). Nephrectomy is done due to both benign and malignant clinical indications as observed in this study. The most common indication was chronic pyelonephritis with the non-functioning kidney.
Keywords: Nephrectomy; Pyelonephritis; RCC